2018
DOI: 10.1111/jcmm.14052
|View full text |Cite
|
Sign up to set email alerts
|

An TRIM59‐CDK6 axis regulates growth and metastasis of lung cancer

Abstract: Lung cancer (LC) is a devastating malignancy with no effective treatments, due to its complex genomic profile. Using bioinformatics analysis and immunohistochemical of lung carcinoma tissues, we show that TRIM59 as a critical oncoprotein relating to LC proliferation and metastasis. In this study, high TRIM59 expression was significantly correlated with lymph node metastasis, distant metastasis, and tumour stage. Furthermore, up‐regulation of TRIM59 expression correlated with poorer outcomes in LC patients. Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Recently, studies indicated that exosomes contain a variety of biologically active molecules including proteins, and that exosomal proteins profiles resemble those of the parent cells [ 9 , 11 ]. We previously found that TRIM59 is closely correlated with oncogenesis and metastasis of lung cancers [ 19 ]. To elucidate whether TRIM59 was expressed in exosomes derived from lung cancer cells (H1299 and A549), we detected the expression of TRIM59 in the exosomes derived from A549 and H1299 cell lines, in which TRIM59 expression levels significantly elevated [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, studies indicated that exosomes contain a variety of biologically active molecules including proteins, and that exosomal proteins profiles resemble those of the parent cells [ 9 , 11 ]. We previously found that TRIM59 is closely correlated with oncogenesis and metastasis of lung cancers [ 19 ]. To elucidate whether TRIM59 was expressed in exosomes derived from lung cancer cells (H1299 and A549), we detected the expression of TRIM59 in the exosomes derived from A549 and H1299 cell lines, in which TRIM59 expression levels significantly elevated [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that TRIM59 is closely correlated with oncogenesis and metastasis of lung cancers [ 19 ]. To elucidate whether TRIM59 was expressed in exosomes derived from lung cancer cells (H1299 and A549), we detected the expression of TRIM59 in the exosomes derived from A549 and H1299 cell lines, in which TRIM59 expression levels significantly elevated [ 19 ]. As is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several members of the TRIM protein family are important regulators of CRC 45 48 . TRIM59 facilitates proliferation of CRC and promotes metastasis via the phosphoinositide 3-kinase/AKT pathway 49 .…”
Section: Discussionmentioning
confidence: 99%